2015
DOI: 10.1260/0309-524x.39.3.299
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of the NREL Phase VI Rotor

Abstract: ABSTRACT:The simulation of the turbulent and potentially separating flow around a rotating, twisted, and tapered airfoil is a challenging task for CFD simulations. This paper describes CFD simulations of the NREL Phase VI turbine that was experimentally characterized in the 24.4m × 36.6m NREL/NASA Ames wind tunnel (Hand et al., 2001). All computations in this article are performed on the experimental base configuration of 0 o yaw angle, 3 o tip pitch angle, and a rotation rate of 72 rpm. The significance of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…For this turbine the flow starts to separate at the inflow speed of 7m/s and goes to massively stalled conditions from the inflow speed of 10 m/s. [4][5][6][7][8] The reported results indicated that for attached flows URANS is able to reproduce the mechanical power and thrust, but for higher wind speeds with flow separation, it over-predicts both quantities. Correspondingly, they showed deviations from the experiment for the force coefficients for different sections along the rotor span.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For this turbine the flow starts to separate at the inflow speed of 7m/s and goes to massively stalled conditions from the inflow speed of 10 m/s. [4][5][6][7][8] The reported results indicated that for attached flows URANS is able to reproduce the mechanical power and thrust, but for higher wind speeds with flow separation, it over-predicts both quantities. Correspondingly, they showed deviations from the experiment for the force coefficients for different sections along the rotor span.…”
Section: Introductionmentioning
confidence: 95%
“…2,3 Although previous inventigations have demonstrated that RANS based models are accurate enough in the pre-stall regime, they are known to be not accurate for predicting the aerodynamic loads for wind turbines in separated flow. [4][5][6][7][8] Flow separation typically occurs when the blade sections are subjeted to high angles of attack, what might take place under a varieties of operating conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the time-dependent aerodynamic loads on the surface of wind rotor were computed by solving the unsteady To obtain better convergence and precise aerodynamic results, full-hexahedral mesh grids of reasonable quality subdivided the entire computational domain by applying the block topology, which can be seen in Figure 2. By adopting the O-grid generation technique [28], mesh refinement was generated near the blade surface to describe with sufficient precision the boundary layer flow, and the size of the first element in the wall-normal direction was fine enough to ensure y + < 5. This y + value made it suitable for the use of the enhanced wall function [29].…”
Section: Numerical Simulation Methods Based On Cfdmentioning
confidence: 99%
“…The effects being studied in this work are largely due to external geometry, so an actuator disk model was deemed sufficient. Detailed RANS simulations of the rotating blades and their trailing vortices have been performed elsewhere but are not required here . The governing equations are utrue¯it+utrue¯jutrue¯ixj0.5em=1ρ0.25emtruep¯xi+xjνutrue¯ixj+()uiujtrue¯xj0.25em+1ρfi1.25emutrue¯ixi=0, where x i represents the position, utrue¯i the mean flow velocity in i ‐direction, truep¯ the averaged pressure, and f i the body force per unit volume acting on the fluid (in particular, this is the axial force in the regions of the actuator disks that mimics drag from the wind turbine).…”
Section: Numerical Setup and Formulationmentioning
confidence: 99%